Consumer Demand for Domestic and Imported Broiler Meat in Urban Ghana: Bringing Non-Price Effects into the Equation - E. Woolverton, Andrea; Frimpong, Stephen (British Journal of Marketing Studies, 2013)
Ghana’s domestic poultry industry is one of many in West Africa that is seeking strategies to compete with imported poultry products. This study investigates if urban Ghanaian consumers are willing to pay for non-price attributes in poultry; hence, offering potential competitive niches. Consumer preferences in Accra, Ghana for domestic and imported chicken were studied using a choice based conjoint analysis. A total of 138 respondents who were directly purchasing broiler products were drawn randomly from both traditional and modern markets for inclusion into a revealed preference data collection. A conditional logistic regression model was used to estimate the part-worth of attributes of both domestic and imported broiler meat. The study reveals that purchase decisions are not entirely based on price, but also non-price attributes such as convenience, freshness and origin of the product. In the case of Ghana, consumers prefer imported chicken on the basis of convenience, as imported chicken is primarily offered as pre-cut pieces, and domestic chicken on the basis of taste and origin. The findings suggest that there is an opportunity to market domestic chicken on attributes in addition to price such as convenience and origin. To take advantage of this opportunity, investment in the domestic poultry industry is required, across the supply chain from processing to marketing.